Evaluation of the impact of security perception on the structural changes of MSEs through system dynamics - Jesabel Gómez Sánchez; Rocío Ramos Hernández; Paula Rosalinda Antonio Vidaña; Ivette Pérez Hernández (Heliyon)
Micro and Small businesses (MSEs) face several challenges to survive in the market, some of these challenges are related to security matters which are the subject of this article. In Mexico MSEs are victims of crimes such as extortion, theft, and assaults, among others; this situation leads them to spend their economic resources to make structural changes to be able to continue with their commercial activities. This article is based on a survey conducted on 370 MSEs in the central region of the state of Veracruz in Mexico; the present study aims to evaluate the impact of structural changes made by businesspeople in their perception of business security. In this way, the decision-making process of MSEs facing insecurity is statistically analyzed through a simulation model considering the system dynamics methodology. To evaluate this phenomenon, we have identified four main subsystems: 1) Crime, 2) Security Perception, 3) Structural Changes, and 4) Government Policy Changes; at the same time three hypothetical scenarios were simulated: 1) Reduction in crimes committed against MSEs, 2) Government changes in public infrastructure, and 3) the combination of the previous two. The approach allows us to identify that companies make structural changes based on the events around them, rather than on the crimes that they suffer, making abrupt or precipitated decisions. Therefore, we have identified that it is not only necessary to eliminate crimes, but also to work with government strategies that allow MSEs owners and staff to improve their perception of security. This simulation model can be replicated to evaluate the implementation of security policies in other regions with high insecurity rates.